1991
DOI: 10.1093/cvr/25.9.742
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in sulphated glycosaminoglycans in aortic dissection--possible role in the pathogenesis

Abstract: The diminution in sulphated glycosaminoglycans and its possible relationship with fat, collagen, and other extracellular matrix molecules could lead to a weakness in the aortic wall related to the dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This suggests that HA and DS may play a role in local alterations within the aortic wall and, in turn, influence altered mechanical properties around the site of dissection. In contrast, another study found a decrease in sulphated GAG content in TAD compared with control [ 27 ]; CS was similar between the groups, whereas HS and DS were decreased. A further study did not identify differences in overall GAG level between control and TAA; however, they did observe differences in the proportion of different sub-types, with increased C6S identified in TAA [ 41 ].…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…This suggests that HA and DS may play a role in local alterations within the aortic wall and, in turn, influence altered mechanical properties around the site of dissection. In contrast, another study found a decrease in sulphated GAG content in TAD compared with control [ 27 ]; CS was similar between the groups, whereas HS and DS were decreased. A further study did not identify differences in overall GAG level between control and TAA; however, they did observe differences in the proportion of different sub-types, with increased C6S identified in TAA [ 41 ].…”
Section: Resultsmentioning
confidence: 86%
“…From the search, 13 papers reported changes in GAGs with age without association with disease. An additional TAAD paper also reported age-related changes in normal tissue [ 27 ]. The majority of studies report total GAGs to increase with age, accompanied by an alteration of ratios of subtypes ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14.1) (Maeso Madronero et al 2000;Leu and Leu 1988). It was first described by Otto Gsell (Gsell 1928) and Jakob Erdheim (Erdheim 1929a, b) as a disease entity of the aortic vascular wall (Guitierrez et al 1991;Hirst and Gore 1976). Pathogenetically, it leads to destruction of the aortic or arterial media with destruction of smooth muscle fibers, mesenchyme, and elastic fibers ( Fig.…”
Section: Dissecting Aortic Aneurysm In Idiopathic Cystic Medial Necrosismentioning
confidence: 99%
“…Avoiding these biases in the selection of cases, our findings are different. In contrast with the histological appearance of mucoid pools (constituted by GAGs), there is a decrease of such compounds in acute aortic dissections [5]. …”
mentioning
confidence: 99%